If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-2(6x-10)=-16+3(5x+4
We move all terms to the left:
3x-2(6x-10)-(-16+3(5x+4)=0
We multiply parentheses
3x-12x-(-16+3(5x+4)+20=0
We add all the numbers together, and all the variables
-9x-(-16+3(5x+4)+20=0
| 2(v-6)=37-5v | | 3x+(2x-3)=72 | | 14-20a=44 | | 12x-18x-2=0 | | 8(k+7)-7k=-2-6 | | n-10=10/12n-7-1/3n | | 5n+15=n+7 | | 44=14-20a | | 8+2x=2+1x | | 9-7m=-3m-7m | | -4x+3(2x-5)=-31 | | 3x-31=2x+12 | | -100=-14v+14v | | 4j+2j=12 | | 30y-40=5(6y-8) | | 225-x=156 | | 7x-3x+6x=50 | | 6x=50+2.80x | | 9x(x+2)+15=-2(6x+5) | | (3+x)/8=7/12 | | 10u=36+6u | | 1+21x=18+0.05x | | -13-4k=7+k | | 7x+19/2=13 | | 90-x/x=x | | 2∧(x+2)=16 | | 7/12x=1/2x | | 251=-x+98 | | 78=9x+12 | | a-1+3a=-1-a | | 9x+12=78 | | 7/12x=3/14+1/2x |